Chemical and metabolic studies on N-benzyl-tert-butylamine and its potential metabolites - (:unkn) unknown (My University, 1995)
The metabolism of N-benzyl-tert-butylamine was studied in vitro using male hamster hepatic microsomal preparations. This substrate produced the corresponding nitrone, benzaldehyde and an uncharacterised metabolite. No metabolites were detected which corresponded to either authentic amide or oxaziridine. The results indicate that the nitrone observed as a metabolite in this experiment is not an intermediate leading to the formation of an oxaziridine and hence an amide, under careful experimental conditions excluding light. © Freund Publishing House, Ltd. 1995
Keywords: hamster; metabolism; microsomes; N-benzyl-tert-butylamine; nitrones; oxaziridines